Taking a Multifoci Approach to the Study of Justice, Social Exchange, and Citizenship Behavior: The Target Similarity Model† - Lavelle, James J.; Rupp, Deborah E.; Brockner, Joel (Journal of Management, 2007)
An emerging trend within the organizational justice, social exchange, and organizational citizenship behavior literatures is that employees maintain distinct perceptions about, and direct different attitudes and behaviors toward, multiple foci such as the organization, supervisors, and coworkers. However, these multifoci developments have progressed, for the most part, independently of one another. Thus, to gain a more complete conceptualization of the employee experience, this review brings these respective literatures together. Specifically, the authors (a) review and organize multifoci research and theory in justice, social exchange, and citizenship behavior, (b) develop a “target similarity” model to provide a theoretical framework for conceptualizing and integrating multifoci research, and (c) o fer suggestions for future multifoci research.